Iʻjāz Al-Quran dan Kesehatan Preventif: Analisis Interdisipliner Tafsir dan Ilmu Medis - Salam, Mohammad Tohir (Yayasan Albahriah Jamiah Indonesia, 2025)
The Quran, as the holy book of Muslims, is not only understood in a theological dimension but also contains scientific messages relevant to health issues, including the concept of disease prevention. The phenomenon of increasing awareness of preventive health in the modern medical world shows the urgency of reviewing the iʻjāz dimension of the Quran as a source of inspiration for a healthy lifestyle. This study aims to analyze Quranic verses containing preventive messages from the perspective of classical and contemporary interpretations, then integrate them with the theories and findings of modern medical science. The research method employed is a literature study with an interdisciplinary approach, involving an interpretive analysis of thematic verses related to diet, hygiene, lifestyle, and psychological health, which is then contextualized with medical studies. The results show that the Quran emphasizes the principle of moderation in consumption (QS. Al-A'raf: 31), which is in line with the concept of balanced nutrition in medical science, as well as the importance of maintaining cleanliness (QS. Al-Baqarah: 222), which is proven to be relevant to the principles of sanitation and infection prevention. Furthermore, regulating rest time and maintaining peace of mind (QS. Al-Furqan: 47; QS. Ar-Ra’d: 28) has been shown to have a positive correlation with mental health and the immune system. The conclusion of this study confirms that the iʻjāz message of the Quran regarding preventive health can serve as a normative and practical framework for strengthening the paradigm of modern prevention-based medicine, thus affirming the relevance of the Quran as a guide to life that encompasses both spiritual and biological dimensions of humans.